Phylogenetic Relationships Within Chrysogorgia (Alcyonacea: Octocorallia), a Morphologically Diverse Genus of Octocoral, Revealed Using a Target Enrichment Approach - Untiedt, Candice Bobby; Quattrini, Andrea M.; McFadden, Catherine S.; Alderslade, Phil A.; Pante, Eric; Burridge, Christopher P. (Frontiers in Marine Science, 2021)
The octocoral genus Chrysogorgia Duchassaing & Michelotti, 1864 contains about 80 nominal species that are ecologically important components of benthic communities. A review of morphological variation within Chrysogorgia identified nine groups that may represent distinct lineages; which would help clarify their taxonomy and guide genus revision. Here, we applied a recently developed universal target enrichment bait method for octocoral exons and ultraconserved elements (UCEs) on 96 specimens varying in morphology, collection ages and DNA quality and quantity to determine whether there was genetic support for morphologically defined groups within Chrysogorgia. Following Illumina sequencing and SPAdes assembly we recovered 1682 of 1700 targeted exon loci and 1333 of 1340 targeted UCE loci. Loci recovery per sample was highly variable and significantly correlated with time since specimen collection (2-60 years) and DNA quantity and quality. Phylogenetically informative sites in UCE and exon loci ranged from 34.75 - 36.10% for 50% and 75% taxon-occupancy matrices, respectively. Maximum likelihood analyses recovered highly resolved trees with topologies supporting the recognition of 11 candidate genera, nine of which are novel. Our results also demonstrate that this target-enrichment approach can be applied to degraded museum specimens of up to 60 years old. This study shows that an integrative approach consisting of molecular and morphological methods is essential in a proper revision of Chrysogorgiath taxonomy and regional diversity of these ecologically important corals.